2022
DOI: 10.1039/d2ma00150k
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured molybdenum dichalcogenides: a review

Abstract: With increasing interests in transition metal dichalcogenides (TMDs), immense literature has come into existence covering broad range of preparation methods as well as applications in diverse fields. Often dichalcogenides include...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 230 publications
0
6
0
Order By: Relevance
“…A van der Waals gap between the layers, affecting the electronic and optical properties of the material, is supported by experimental evidence, such as scanning tunneling microscopy and X-ray diffraction studies, which have shown a clear separation between the layers in TMDs [ 30 ]. On the other hand, some studies have suggested that there may be voids rather than a gap between the layers in TMDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A van der Waals gap between the layers, affecting the electronic and optical properties of the material, is supported by experimental evidence, such as scanning tunneling microscopy and X-ray diffraction studies, which have shown a clear separation between the layers in TMDs [ 30 ]. On the other hand, some studies have suggested that there may be voids rather than a gap between the layers in TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the weak bonds between adjacent layers, TMDs can be thinned down to single layers [ 27 , 28 ]. The weak interlayer adhesion is caused by the presence of a gap or voids between the layers and is still a matter of debate in the scientific community [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the already discovered and intensely studied classes of 2D materials-such as special element allotropes [1,2], transition metal dichalcogenides [3,4], or MXenes [5,6]-the group of transition metal trihalides with 2D crystal structures hosts numerous compounds with unique and exotic properties, especially when their structures are scaled down to nanometer dimensions. To name just a few, RuCl 3 is featured in countless studies for its potential as a Kitaev quantum spin liquid ground state [7,8], CrX 3 (X = Cl, Br, I) exhibit interesting switches of their magnetic properties during downscaling [9][10][11], or the catalytic activity of TiCl 3 is to improved when downscaled [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies address the fact that transitional metal chalcogenides, metal nitrides, and metal carbides have great benefits in HER due to their high activity, availability, and notable stability. Specifically, molybdenum dichalcogenides (MDC, MoX 2 , X = S, Se, and Te) are decent examples of active electrocatalysts because of their structural morphology as well as chemical properties. , However, their catalytic efficiency is suffocated by two major limitations, i.e., less active edge parts or inactive basal sites and the weak electric transfer ability of the catalyst . To nullify these problems, researchers have focused on some important keys.…”
Section: Introductionmentioning
confidence: 99%